Empathy-based teaching English and strategies their impact on motivation and meaningful learning. (2022)
This graduation paper is action research whose research objective is "Determine how empathy-based Teaching strategies transform students' motivation and meaningful language learning process that focuses on concepts such as empathy, teaching strategies, the role of the teacher, motivation, and meaningful learning. In this research study, different data collection instruments were used (interview/query, observation) through an interactive technique such as the focus group; For the analysis and interpretation of the data, the characterization, cutting, coding, and categorization were taken into account in order to find the most significant findings, among them “Empathy as a learning strategy to develop the human dimensions in the English classroom. Empathy as a teaching strategy to strengthen diversity in the English classroom. The development of empathy in the English classroom and its impact on motivation and meaningful learning. Empathy as social construction among teachers and students”. Additionally, this article constantly reflects on the teaching role based on empathy and the constant adaptation to changes for more humanistic teaching for students both for their needs, academic development, and social interactions.